Optimasi Jumlah Produksi Kue Karawo pada UMKM Yayu Al Menggunakan Program Linear dan Aplikasi Mathway - Valentina Monoarfa; Alfian Tobi; Jian Fitri Tumulo; Lina Putri Taufik; Muzdaliva Monoarfa; Cindy Aniga; Amanda Hatibae (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Yayu Al's UMKM is a cake shop that sells various types of karawo cakes. As the culinary industry in Gorontalo develops, the competition in this sector is getting tougher, especially for karawo cakes. Therefore, creativity is needed for the company to survive and be at the forefront of its field. The purpose of this study is to analyze and determine the optimal amount of production to get maximum profit. The research method used is mixed methods using observation and interview approaches, and data analysis using linear programs and mathway applications. The results obtained are that UMKM Karawo Yayu Al Cake can use linear programs with the help of graphs from Mathway application for decision making. The calculation results show that the Tulip Chocolate Karawo Cake has the highest production capacity, which is 6,600, with a significant potential contribution to UMKM.